Expression profiles of immune-related genes are associated with neoadjuvant ipilimumab clinical benefit. (1st February 2017) - Tarhini, Ahmad A.; Lin, Yan; Lin, Hui-Min; Vallabhaneni, Priyanka; Sander, Cindy; LaFramboise, William; Hamieh, Lana
ABSTRACT: Purpose : Patients with regionally advanced melanoma were treated with neoadjuvant ipilimumab in a previously reported study (PLOS One 2014). Gene expression profiles of tumors of treated patients were investigated for their association with immunotherapeutic benefit.Methods : Patients were treated with ipilimumab (10 mg/kg intravenously every 3 weeks × 2 doses) before and after surgery. Tumor specimens were obtained at baseline and at definitive surgery (weeks 6–8). Gene expression profiling was performed on the tumor biopsies of 27 patients. The primary endpoint was mRNA expression profiling using U133A 2.0 Affymetrix gene chips. Significance analysis of microarrays was performed to test the association of each gene with outcome. Pathway analysis was performed using Ingenuity Pathway Analysis software. The Benjamini and Hochberg method was used to adjust for multiple testing in the pathway analysis.Results : Pathway analysis identified biologically relevant pathways enriched with genes that are significantly associated with clinical outcome at baseline in relation to relapse-free survival (RFS) and disease non-progression (as assessed preoperatively at week 6) as well as early on-treatment (RFS and overall survival). The molecules and pathways that achieved differential expression of highest statistical significance were notably immune related. Association of the gene signature with clinical outcome overlapped between baseline and on-treatment specimens and across clinical endpoints tested.Conclusion : Gene expression profiling identified a signature reflecting an immune active and proinflammatory tumor microenvironment that derived clinical benefit from neoadjuvant ipilimumab at baseline and early on-treatment. These findings warrant further investigation in relation to ipilimumab and other immunotherapeutics.